The Immunohistochemical Profile of Superoxide Dismutase (SOD) in the Liver Tissue of Hypercholesterolemic Rats - TUTIK WRESDIYATI; MADE ASTAWAN; LUSIA YUNI HASTANTI (Bogor Agricultural University, Indonesia, 2006)
This study was conducted to observe intracellular antioxidant cooper,zinc-superoxide dismutase (Cu,Zn-SOD) in liver tissue of rats under hypercholesterolemic condition by using immunohistochemical technique. A total of twenty male Wistar rats were used for this study. Those rats were divided into two groups; (i) control group and (ii) hypercholesterolemic group, which were fed died containing 1% cholesterol for eight weeks. Rat livers were taken at the end of treatment, and processed by using paraffin embedding standard method. The tissues were stained immunohistochemically to Cu,Zn-SOD. Observation of Cu,Zn-SOD content in the tissue was performed qualitatively in the cytoplasm and quantitatively in the nucleus of hepatocytes based on colour intensity of enzyme reaction product. The profile of antioxidant-Cu,Zn-SOD decreased (P < 0.05) in the hypercholesterolemic group compared to the control group. Key words: Superoxide dismutase (SOD), hypercholesterolemia, liver, rat